Anti-platelet aggregation activities of different grades of Angelica sinensis and their therapeutic mechanisms in rats with blood deficiency: insights from metabolomics and lipidomics analyses - Xue Shen; Yangyang Wu; Ping Chen; Yuwei Bai; Yanan Liu; Yihan Jiang; Yawen Zhang; Yawen Zhang; Zhigang Yang; Zhigang Yang; Zhigang Yang (Frontiers Media S.A., 2024)
In traditional Chinese medicine, the radix of Angelica sinensis (Oliv.) Diels (RAS) is mainly used to replenish and invigorate the blood circulation. This study investigated anti-platelet aggregation activities were used by New Zealand rabbits, and high-performance liquid chromatography data were obtained to determine the spectrum-effect relationship for different commercial grades of RAS. Plasma and urine metabolites were examined using ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry-based metabolomics to elucidate the mechanisms underlying the role of these metabolites in a rat model of blood deficiency (BD). Plasma and spleen metabolites were additionally examined using ultra-performance liquid chromatography plus Q-Exactive tandem mass spectrometry-based lipidomics to clarify the mechanisms of RAS in treating BD. The third grade of RAS exhibited the best activity in replenishing and invigorating blood in vitro and in vivo. Ferulic acid, ligustilide, senkyunolide I, uridine, and guanine are quality markers of anti-platelet aggregation activity. Based on the metabolomics results, 19 potential biomarkers were screened in plasma, and 12 potential metabolites were detected in urine. In lipidomics analyses, 73 potential biomarkers were screened in plasma, and 112 potential biomarkers were screened in the spleen. RAS may restore lipid metabolism by regulating disorders of glycerophospholipid and sphingolipid metabolism, the tricarboxylic acid cycle, amino acid metabolism (thereby improving energy metabolism), and arachidonic acid metabolism (thereby promoting blood circulation). These results provide a deeper understanding of the effects of different grades of RAS and a scientific reference for the establishment of grading standards and for the clinical use of RAS.